Clinical study and management of incisional hernias: a prospective monocenter experience - Deshmukh, Santoshkumar N.; Varudkar, Anagha S.; Chopde, Anant V. (International Surgery Journal, 2017)
Background: Incisional hernia is the most frequent postoperative complication following abdominal surgery. Several studies have shown that incisional hernias have different etiologies which are related to the patient, the surgical technique, the suture material, and experience of the surgeon. Aim of present study was to assess the magnitude of problem, analyse various factors leading to development of this condition, different modalities of treatment practiced, postoperative complications, various factors affecting surgical outcome in these patients. Methods: This prospective descriptive study was conducted in department of surgery at a tertiary care teaching hospital at Solapur, Maharashtra, India from January 2014 to December 2016. All the patients, regardless of age and gender, admitted with diagnosis of incisional hernia were included in the study. Depending upon the size of defect treatment was carried out. Postoperatively patients were followed up for detection of possible complications and their treatment. Results: Total 50 patients of incisional hernia were studied. Mean age was 46 years with male to female ratio 4.5:1 wound infection in the post-operative period was the commonest etiology noted followed by obesity. Conclusions: Wound infection following previous surgery was the most important risk factor associated with incisional hernia. The other risk factors were obesity and COPD. Polypropylene mesh repair is superior to anatomical repair as it has less recurrence.